Maqāṣidī Exegesis: A Path for Promoting Gender Equality in Contemporary Islamic Discourse - Affandi, Abdullah; Billah, M. Mu'tashim; Syaifudin, Muh. (QOF, 2025)
This research explores the potential of maqāṣidī exegesis as a framework for interpreting the Qur'an that can promote gender equality in contemporary Islamic discourse. Starting from the reality that classical exegesis often reflects patriarchal social constructs, this study offers an alternative approach that emphasizes the main objectives of Islamic law (maqāṣid al-sharī‘ah), such as justice, welfare, and the protection of human dignity. Using qualitative content analysis, comparative analysis, and a hermeneutic approach, this study examines several key verses related to gender—including polygamy, inheritance, testimony, and qiwāmah—through the lens of maqāṣidī. The research findings indicate that this approach not only reconstructs the understanding of gender relations in Islam in a more just and equitable manner but also challenges the patriarchal interpretative legacy that has been entrenched in the tradition of exegesis. The novelty of this study lies in the systematic application of maqāṣidī exegesis to gender issues comprehensively, not merely through a feminist approach, but by asserting that the values of gender justice are inherent in maqāṣid al-sharī‘ah itself. These findings provide a conceptual contribution to the development of value-based and ethical Islamic exegesis. They are relevant for reforming Islamic law to be more responsive to contemporary social dynamics.